Effect of steric hindrance on the interfacial connection of MOF-on-MOF architectures. Issue 7 (20th March 2023) - Ha, Junsu; Jeon, Mingyu; Park, Jihyun; Kim, Jihan; Moon, Hoi Ri
Abstract : This work investigates how the interfacial strain effects occur in an interface of a MOF-on-MOF. The series of synthetic experiments and computational results revealed the importance of the proximity in each chemical connection point in a MOF-on-MOF system. Abstract : MOF-on-MOF is attracting great attention due to its improved and/or synergistic properties not exhibited in a single MOF. In particular, the non-isostructural pairs of MOF-on-MOFs can have great potential induced by large heterogeneity, which enables diverse applications in a wide range of fields. HKUST-1@IRMOF is a fascinating platform because the alteration of the IRMOF pores with bulkier substituent groups on the ligands can provide a more microporous environment. However, the sterically hindered linker can affect the seamless growth at the interface, an important issue in practical research fields. Despite many efforts to reveal the growth of a MOF-on-MOF, there is still a lack of studies on a MOF-on-MOF consisting of a sterically hindered interface. Indeed, the effect of a bulky linker at an interface of HKUST-1@IRMOF, a non-isostructural MOF-on-MOF system, has not yet been reported, and thus, how the interfacial strain affects the interfacial growth remains unknown. In this study, we investigate the effect of an interfacial strain on a chemical connection point in an MOF-on-MOF system through a series of theoretical and synthetic experiments using a HKUST-1@IRMOF system. Our results reveal the importance of the proximity of each coordinating site at a MOF-on-MOF interface as well as lattice parameter matching for an effective secondary growth to achieve a well-connected MOF-on-MOF.